Quantifying Optimal Policy in an Endogenous Growth Model: A Theoretical Analysis (Global Journal of Management and Business Research, 2019)
This paper aims to characterize the optimal growth path of an endogenous growth model with domestic innovation, human capital and external technology spillovers through import of technologically advanced products and foreign direct investments. There are three sources of inefficiency in the model; monopolistic competition in the intermediate-goods sector, duplication externalities and spillovers in R&D. This raises the question of whether an adequate government intervention can provide the required incentives to correct these inefficiencies and make the decentralized economy to replicate the first-best solution attainable by a social planner. In this study, we find that the first-best optimum can be decentralized by means of a tax on capital income at a constant rate combined with equality between the share of public spending in the total expenditure on education net of subsidy and the tax on labor income and a time-varying subsidy to R&D. Unlike previous works that focus solely on the steady state, we take explicitly into account the transitional dynamics as well.
Keywords: endogenous growth; R; social planner; monopolistic distortions; optimal policy